2023
DOI: 10.3389/fcimb.2023.1136056
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of signal peptidase complex expression affects the development and survival of Schistosoma japonicum

Abstract: BackgroundSchistosomiasis, the second most neglected tropical disease defined by the WHO, is a significant zoonotic parasitic disease infecting approximately 250 million people globally. This debilitating disease has seriously threatened public health, while only one drug, praziquantel, is used to control it. Because of this, it highlights the significance of identifying more satisfactory target genes for drug development. Protein translocation into the endoplasmic reticulum (ER) is vital to the subsequent loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…SjFer1 and 2 did not affect growth or development [60]. More recently, investigations on the role of the signal peptidase complex (SPC), an essential part of protein translocation machinery, revealed that the in vivo knockdown of the SPC25 gene led to the degeneration of reproductive organs and reduced egg production, reducing damage in the host [61].…”
Section: Rnai In Vivomentioning
confidence: 99%
“…SjFer1 and 2 did not affect growth or development [60]. More recently, investigations on the role of the signal peptidase complex (SPC), an essential part of protein translocation machinery, revealed that the in vivo knockdown of the SPC25 gene led to the degeneration of reproductive organs and reduced egg production, reducing damage in the host [61].…”
Section: Rnai In Vivomentioning
confidence: 99%